Toward National Well-Being Accounts - Kahneman, Daniel; Krueger, Alan B; Schkade, David; Schwarz, Norbert; Stone, Arthur (American Economic Review, 2004)
Toward National Well-Being Accounts by Daniel Kahneman, Alan B. Krueger, David Schkade, Norbert Schwarz and Arthur Stone. Published in volume 94, issue 2, pages 429-434 of American Economic Review, May 2004